オーロラ ノ ブンルイ ト ショウワキチ フキン ニオケル キョクコウタイ ノ イチ - 中村, 純二; ナカムラ, ジュンジ; NAKAMURA, Junji (国立極地研究所, 1961)
P(論文) 1959年日本南極第3次越冬隊は,昭和基地に於ていくつかのオーロラの光学的観測を行なった.観測地点は南緯69度00分,東経39度35分,高度14米である.全天カメラのフィルムと分光器のフィルムを統計的に調べることにより,オーロラ最頻度帯は昭和基地の南方に位置すること,ならびにオーロラは大別して,(a)黄緑色のもの,(b)下縁の赤いもの,ならびに(c)上部赤或いは全部赤いものの3種類に分けられることが明らかとなった.極光帯の位置はこれら3種類のオーロラの各々について少しずつ異なり,又局所時によってもその位置を変えることが判明した. In 1959 III JARE (the third Japanese Antarctic Research Expedition) performed several optical observations of aurora at Syowa Base which is located at 69°00'S, 39°35'E and 14m above sea level. From statistical treatment of the all sky camera films and spectra, it has become known that the auroral maximum zone lies to the south of Syowa Base and aurora can be classified into the following three types (a) yellow-greenish aurora, (b) aurora with red lower border, and (c) entirely red aurora or only the upper part red. It has also been unraveled that the position of auroral zone may be distinguished by its type and the position of each zone varies with local time. departmental bulletin paper